2018
DOI: 10.22214/ijraset.2018.1039
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Evaluation of Power Driven Piston Type Multi-crop Chipper

Abstract: Power-driven piston type multi-crop chipper was designed to improve chipping operation of micro, small-scale and medium (MSMEs) chip processors, to introduce new mechanism different from the existing conventional chippers, and develop a low costs, efficient and easy to operate and maintain chipping machine fabricated out of locally available materials. The machine was driven by 0.5 hp electric motor and was made up of dual chipping section to upscale chipping capacity. It was composed of blade plate and blades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Sonawane's research [13] concluded that at 360 rad s -1 , it could produce an efficiency ranging from 93 % to 94 % and a capacity of 100 kg h -1 by using an electric motor 1 HP or 2 HP. The piston model suppression system was developed by Magpili et al [14] and Hatwar et al [15] for a more stable cut than being pushed by hand. The success rate using piston-type plungers can reach an efficiency of 95.63 % [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonawane's research [13] concluded that at 360 rad s -1 , it could produce an efficiency ranging from 93 % to 94 % and a capacity of 100 kg h -1 by using an electric motor 1 HP or 2 HP. The piston model suppression system was developed by Magpili et al [14] and Hatwar et al [15] for a more stable cut than being pushed by hand. The success rate using piston-type plungers can reach an efficiency of 95.63 % [14].…”
Section: Introductionmentioning
confidence: 99%
“…The piston model suppression system was developed by Magpili et al [14] and Hatwar et al [15] for a more stable cut than being pushed by hand. The success rate using piston-type plungers can reach an efficiency of 95.63 % [14].…”
Section: Introductionmentioning
confidence: 99%